Vegetation patterns in a South American coastal wetland using high-resolution imagery - Gonzalez, Eliana Belen (2019)
The aim of this study was to map and describe marsh patterns in a temperate coastal wetlands with high resolution imagery. We carried out a map of Samborombon Bay at 1:25,000 scale (central coordinates: 36º S 56º W, area: 320.25 km2) by using a WorldView-2 image acquired on November 17, 2010. An Object Based Image Analysis approach was chosen, and an unsupervised classification algorithm was applied. Overall classification accuracy was 81% and the Kappa index was 78.1%. We found four spatial patterns at a landscape scale. The lower intertidal was dominated by mudflats without vegetation in the exterior and middle estuary (patterns 1 and 2) and Bolboschoenus maritimus in the inner estuary (pattern 4). The middle intertidal was dominated by Sarcocornia ambigua in the four patterns while the higher intertidal was dominated by Spartina densiflorus and grasslands with Cortaderia selloana (pattern 3). The map allowed the discrimination of plant communities at a landscape scale and became a valuable baseline for future studies on wetland environmental indicators.